Future-Proof CALL: Language Learning as Exploration and Encounters – Short Papers From EUROCALL 2018 2018
DOI: 10.14705/rpnet.2018.26.824
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes toward high-immersion virtual reality assisted language learning

Abstract: This pilot study delivers a preliminary report on students' attitudes toward Virtual Reality Assisted Language Learning (VRALL). Learners (N=22) participated in a VRALL lesson and then completed a post-experience survey. Virtual Reality (VR) technology allows for learning experiences that increasingly remove geographic limitations to foreign language learners. Thanks to multisensory features of VR, including 360-degree, three-dimensional visualizations, students' experiences are highly immersive. Descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…For example, Berti (2019) described the process of developing 360° VR videos to teach Italian and analyzed students’ reflections of the materials gleaned from surveys. Students’ perceptions were also reported by Kaplan‐Rakowski and Wojdynski (2018) who created simulations in 360° visualizations. L2 English learners who interacted with people in various roles reported that their VR experience was engaging.…”
Section: Introductionmentioning
confidence: 76%
“…For example, Berti (2019) described the process of developing 360° VR videos to teach Italian and analyzed students’ reflections of the materials gleaned from surveys. Students’ perceptions were also reported by Kaplan‐Rakowski and Wojdynski (2018) who created simulations in 360° visualizations. L2 English learners who interacted with people in various roles reported that their VR experience was engaging.…”
Section: Introductionmentioning
confidence: 76%
“…Students seemed to have a mostly favorable view of both types of meditation, with a preference for VR. Reporting a positive attitude toward VR technology is a common finding (see, for example, Kaplan-Rakowski & Wojdynski, 2018 ), given that VR technology was novel to most students. In fact, for several decades now, scholars have pointed out that novelty may lead to the mistaken belief that learning is attributed to a particular technology (e.g., Clark, 1983 ) and that technology can be VR as well (Huang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-immersion VR is a beneficial platform to manage attention (Hoffman et al, 2001 ). As VR has become more affordable and accessible, the technology is being widely used in education and training to motivate students and enhance the learning process (Freina & Ott, 2015 ; Kaplan-Rakowski & Wojdynski, 2018 ). Although still in its infancy, VR meditation is used as a tool in educational and training settings to motivate students in the learning process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, CMC tools (e.g., SMS, chat, blogs, and video conferencing) can offer space for learners to directly interact with users of the target language across distances (Cunningham, 2019;Li, 2019;Tang, 2020). Digital games and virtual reality (VR) space (both desktop and immersive VR) can provide interactive and immersive environments where learners simulate different roles in diverse social settings (Holden & Sykes, 2013;Kaplan-Rakowski & Wojdynski, 2018;Sykes, 2009Sykes, , 2013Taguchi, 2021;Vilar-Beltrán & Melchor-Couto, 2013; for a review, see Blyth, 2018;Lan, 2020;Sykes & Dubreil, 2019). In these environments, learners can directly participate in an interactional situation rather than observing the situation as a third person.…”
Section: Technology-mediated Pragmatics Learning and Teachingmentioning
confidence: 99%